2005
DOI: 10.1007/11552499_53
|View full text |Cite
|
Sign up to set email alerts
|

3D Model Retrieval Based on Adaptive Views Clustering

Abstract: In this paper, we propose a method for 3D model indexing based on 2D views, named AVC (Adaptive Views Clustering). The goal of this method is to provide an optimal selection of 2D views from a 3D model, and a probabilistic Bayesian method for 3D model retrieval from these views. The characteristic views selection algorithm is based on an adaptive clustering algorithm and using statistical model distribution scores to select the optimal number of views. Starting from the fact that all views do not contain the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…The problem of this approach is in the choice of: Normalization of the pose, the projection area, the size of image, the nature of the 2D shape descriptors and the size of the signature. The authors (Ricard et al, 2005;Ansary et al, 2005;Mahmoudi and Daoudi, 2002;Nidhal and Lamis, 2014) have proposed methods of optimal selection of 2D views to represent a 3D model. Each 3D object is represented by a view set called the characteristic views.…”
Section: Approach Based Viewsmentioning
confidence: 99%
“…The problem of this approach is in the choice of: Normalization of the pose, the projection area, the size of image, the nature of the 2D shape descriptors and the size of the signature. The authors (Ricard et al, 2005;Ansary et al, 2005;Mahmoudi and Daoudi, 2002;Nidhal and Lamis, 2014) have proposed methods of optimal selection of 2D views to represent a 3D model. Each 3D object is represented by a view set called the characteristic views.…”
Section: Approach Based Viewsmentioning
confidence: 99%
“…But the large number of viewpoints also give rise to the problems as follows: 1) a lot of information redundancy occurs in the collection of the 2D views due to the overlap between the view coverage of adjacent viewpoints; 2) the pair-wise comparison of the 2D views taken from the viewpoints is quite time consuming. Several approaches have been proposed to address these issues, including the adaptiveview-clustering method reported by Ansary et al [13], the view-context method reported by Li et al [14] and the probabilistic-graphical-matching method in [12].…”
Section: Introductionmentioning
confidence: 99%
“…The dissimilarity between two 3D models is defined as the minimal dissimilarity of the silhouettes over all rotations and all pairs of vertices on the corresponding dodecahedrons. Filali Ansary et al [7] introduce a novel probabilistic Bayesian using a characteristic views selection. Curvature scale space (CSS) descriptor is used in [8].…”
Section: Introductionmentioning
confidence: 99%